The role of the EU's European Neighbourhood Policy in promoting and protecting democracy, the rule of law and human rights in Ukraine - Lemishka, Romana (2019)
This thesis offers an analysis of the effects that the European Neighbourhood Policy (ENP) has had on the promotion and protection of democracy, the rule of law and human rights in Ukraine. It examines the application of four methods under the ENP: i) positive conditionality, ii) negative conditionality, iii) socialisation, and iv) reform assistance and support of civil society. Internal and external factors and actors that have negatively affected reforms in Ukraine are considered. The thesis explores the evolution of EU-Ukraine relations before and under the ENP. Specific instruments at the EU’s disposal under the four methods are analysed. Against that background, the application and effects of the four methods are evaluated along different stages of EU-Ukraine relations. The positive effects and shortcomings of the ENP methods in relation to democracy, the rule of law and human rights in Ukraine are identified.